The Influence of Promotion and Tourist Attraction on Tourists' Revisit Interest at Wadu Jao Beach, Dompu Regency - Cici Cici; Ega Saiful Subhan; Lilis Marlina (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to analyze the Influence of Promotion and Attraction on Tourists' Revisiting Interest at Wadu Jao Beach, Dompu Regency. This quantitative research technique utilizes primary and secondary sources of information. A total of 60 participants became the research sample, selected using the Hair et al. algorithm. After the data was collected, SPSS 23.00 For Windows was used to analyze it. The results of this study indicate that 1). Promotion has a positive and significant effect on Tourists' Revisiting Interest at Wadu Jao Beach. 2). Attraction has a positive and significant effect on tourists' revisiting interest at Wadu Jao Beach. 3). Promotion and attraction together have a positive and significant effect on tourists' revisiting interest at Wadu Jao Beach.